THE IMPACT OF E-SERVICE QUALITY AND PERCEIVED RISK ON TRUST IN BANKING SERVICES - Andhika, Stanly Reza; Qomariah, Nurul (Dynamic Management Journal, 2024)
The world of banking is still the driving force of the national economy today by channeling funds to third parties. To be able to win the competition, banks must be able to maintain the trust of their customers. The design of this research aims to determine the impact of e-service quality and perceived risk on trust in BRI Jember Branch. The population in this research is planned to be all customers of Bank BRI Jember Branch. The sample design was 75 respondents. The data analysis method is to use descriptive analysis. Validity tests and reliability tests are used to test research measuring instruments. Multiple linear regression analysis was used to test the research hypothesis. The results of this research are expected to show that e-service quality and perceived risk can increase customer trust in BRI Jember Branch.